Enforcement of the international treaty in the national legal system and its impact on the sovereignty of the state - Lecturer Dr. Bassem Gnawi Alwan (The college of law and political science journal, 2023)
The rules of international law were established on the basis of respect for the sovereignty of states, whether at the international or national level, but this sovereignty is no longer absolute, So it became restricted by the need to respect the rules of public international law, Although countries are striving steadily to protect and adhere to their national law Since this is a manifestation of their sovereignty, we find that the majority of countries seek to harmonize their internal legislation with the rules of international law, the matter is no problem unless there is a conflict between these legislations, so we find that countries differ among themselves in dealing with this issue. Some countries make international treaties a higher rank than their national legislation, while other countries go to make international treaties a higher rank than the country's constitution itself, and the majority of countries make the rules of international treaties equal to the rank of internal legislation. This raises the problem of the relationship between international treaties and national law. The reference in this is the state's constitution itself, which often determines the legal value of international treaties in the face of  national legislation.